ATTRIBUTES OF EFFECTIVE FOREIGN LANGUAGE TEACHERS: INSIGHTS FROM UKRAINE - Marianna Levrints (Lőrincz); Svitlana Myshko; Kateryna Lizák (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2021)
The paper set out to explore pre-and in-service foreign language teachers' perceptions of attributes of effective teachers in Ukraine within a framework developed by the authors of the study to unravel the construct of effective language teaching. Two groups of pre-service (n=105) and in-service (n=127) teachers were recruited using a snowball sampling technique. The independent samples t-test and MANOVA statistical procedures were utilised to analyse and compare data generated from a self-report questionnaire. The findings indicated that the highest value was assigned to the performance category of teacher effectiveness, followed by the prerequisite category, including teacher competence, with the lowest value attached to the output category. A considerable degree of convergence was observed in students' and teachers' views on many attributes of teacher effectiveness.  Both groups endorsed such attributes as clear teaching, target language proficiency, knowledge of language pedagogy, active engagement of learners, downplaying the importance of learners' test scores. Nevertheless, a statistically significant difference was detected between the perceptions of the two groups of subjects. The students accentuated teachers' personality and rapport domains, as well as motivating instruction. They also endorsed traditional approaches to language teaching in giving preference to form-focused instruction. Conversely, the teachers associated effective teaching with competence, careful planning and ongoing professional development. Teachers gave precedence to current methodological approaches in favouring meaning-focused instruction. A conclusion was drawn that teachers form more sophisticated cognitions of effective teaching in the process of professional maturation, thus implying the necessity for closer attention to the development of prospective teachers' cognitions in teacher education programmes.